Effectiveness Of Education And Basic Training Expert Agriculture 2014 In Secretariat Of Extension Coordination Bengkulu Province - Novianti Novianti; Satria Putra Utama; Septri Widiono (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
The objectives of this research to measure the effectiveness and analyze the factors that influence the effectiveness of basic training agricultural extension experts organized by the Secretariat Bakorluh Bengkulu Province. This research was conducted in March through June 2015 and used slovin methods. The study population was defined as many as 36 people of 40 people from the extension of existing civil servants. Data analysis was done by using tobit models. The results showed that : 1) some characteristics of extension that is age and work experience significantly influence the effectiveness of training 2) several factors including the method of training, facilities and trainers significantly influence the effectiveness of training. 3) The level of effectiveness basic education and training of agricultural extension experts by secretariat of Bakorluh Bengkulu province in middle category or sufficiently effective;.